Effectiveness of field simulation approach for problem-based learning that incorporates the One Health concept - Mustaffa-Kamal, Farina; Shafie, Intan Nur Fatiha; Zakariah, Siti Zulaikha; Wan Mohd Sanusi, Wan Nor Syaheera; Omar, Zoharah; Azahar, Aizad; Amin Nordin, Syafinaz; Omar, Sharina; Ahmad, Nur Indah; Abd Samad, Rozanah Asmah; Shamsuddin, Mohd Shafarin; Arshad, Siti Suri (University of Toronto Press, 2024)
One Health problem-based learning (PBL) is known as an effective method in teaching zoonotic diseases. However, the classic classroom setting limits real-life exposure for students. Simulation-based learning may improve the learning experience without exposing the students to unnecessary risks. Hence, this study aimed to assess the effectiveness of field simulation PBL compared to a classic classroom setting using a module developed based on the One Health concept by examining the students’ reactions towards the learning and by assessing the students’ performance. A quasi-experimental design was adopted in this study. Veterinary and medical undergraduate students participated in both types of PBL settings, and their knowledge and satisfaction were evaluated through a pre- and post-test as well as a feedback survey. The mean satisfaction score of students undergoing field simulation was significantly higher than the mean satisfaction score of students undergoing classic PBL (P>0.05). The respondents from both programmes found the field simulation, in comparison to classic PBL, was more effective, and they were more satisfied with the overall learning experience, workloads, and facilitation. The attainment of the cognitive domain was comparable between both PBL groups which possibly due to the type of assessment used. In conclusion, field simulation enhanced the students’ positive learning experiences as they exhibited better attitudes towards learning. Future studies on the impact of the simulation on long-term knowledge retention and psychomotor skills are thus warranted. Keywords: One Health, problem-based learning, field simulation, veterinary medicine, medicine